Effect of A-site modification on electrical properties and chemical stability of Ba1-xCaxCe0.5Zr0.3Y0.2O3-δ proton-conducting electrolyte. Issue 7 (1st April 2023) - Zhou, Gaopeng; Li, Ying; Luo, Yadan; Huang, Wenlong; Li, Bo
Abstract: This article investigates the substitution effect of different Ca 2+ concentrations at A-sites in perovskites like yttrium and zirconium co-doped with barium cerate. This study focuses on the electrical properties and chemical stability of synthesized materials. With the help of solid-state reaction, different variants of Ba1- x Ca x Ce0.5 Zr0.3 Y0.2 O3-δ (with values of x being 0, 0.02, 0.05, and 0.1 in succession) were obtained, which are also referred to as BC x CZY (where x takes the values 0, 2, 5, and 10 one at a time) in forthcoming discussion. X-ray diffraction results indicate that the group of BC x CZY (with x  = 0, 2, 5, and 10) was synthesized successfully, and according to the energy dispersive spectrometer, the second phases in BC5CZY and BC10CZY were observed. Combined with literature analysis, the second phase of BC5CZY and BC10CZY is determined as BaCa2 Y5 O12 and Y2 O3, respectively. Scanning electron microscopy images illustrate that the density improved with increased Ca 2+ concentration. BC2CZY and BC5CZY samples show better chemical stability in CO2 and humid atmospheres than Ca-free samples. It means chemical stability improves with the proper Ca 2+ concentration. The alternating current (AC) impedance analysis obtained the conductivities of electrolyte pellets in various atmospheres and temperatures. The total conductivities ( σ t o t ) of Ca-substituted BC x CZY pellets are lower than that of unsubstituted BCZY pellets and decrease with increased Ca 2+ concentration. The defect equilibria model was utilized to calculate the partial conductivities. The results show that the proton conductivity of each sample is nearly constant at pH2 O = 0.024 atm and pO2  = 0.2 atm. The transference numbers of protons are dominated in 500–750 °C temperature regions and increase with the Ca 2+ concentration. In a low pH2 O atmosphere, BC10CZY exhibits conductivity with both electron holes ( h ∙ ) and oxide ions ( v O ∙ ∙ ). In contrast, at high pH2 O values, the primary carriers are protons ( O H O ∙ ). The total conductivities of Ca-substituted pellets decrease with an increase in proton transference number.